Avaliação da atividade biológica do eugenol frente cepas de Penicillium citrinum - Araújo, Emmanuel Melquíades (2023)
Fungi of the genus Penicillium have a wide distribution and are frequently isolated in environments ranging from crops to hospitals. Its species are implicated in several pathologies, such as penicilliosis, which mainly affects immunocompromised individuals. Considering this, and the high fungal resistance to current antifungals, the search for new antifungal agents has been encouraged. For this, medicinal plants and their phytoconstituents have been investigated. Based on this, the objective was to evaluate the biological activity of eugenol against strains of Penicillium citrinum. For this, tests were carried out to determine the Minimum Inhibitory Concentration (MIC); Minimum Fungicide Concentration (CFM); effect of the association between eugenol and the standard antifungal amphotericin B; action of products on the fungal cell wall: test with sorbitol and action of products on the cell membrane: interaction with ergosterol. Furthermore, the in vitro cytotoxic effect of eugenol on human erythrocytes was evaluated. Moreover, eugenol was submitted to online software (pkCSM and Osiris) to preview druggability and toxicity parameters. Likewise, molecular docking was performed in AutoDock 4.2 with the proteins involved in the synthesis and maintenance of the P. citrinum cell membrane. Therefore, strong antifungal activity was observed on all strains of Penicillium citrinum evaluated, since the MIC determined was 1 μg/mL and the CFM was 1 μg/mL, demonstrating fungicidal action. Furthermore, the persistence of the MIC of eugenol in the presence of sorbitol and ergosterol revealed that this molecule possibly does not directly affect the integrity of the wall and plasma membrane of Penicillium citrinum. In the association study between eugenol and amphotericin B, it was found that they had an indifferent effect. In silico studies, eugenol presented important oral bioavailability and mutagenic risk, however it was not cytotoxic in the evaluation of the hemolytic potential in human erythrocytes. Molecular docking proposes the predictive hypothesis that eugenol possibly binds to the active site of CYP51, the enzyme responsible for the biosynthesis of ergosterol, thus suggesting that the tested product acts directly on the formation of ergosterol in the fungal cytoplasmic membrane. Therefore, the evidence from this research indicates that eugenol is a promising and possible option for the treatment of fungal infections caused by Penicillium citrinum, and also in the processes of contamination by the fungus in vegetable crops.